A plan-based causal decision theory. (25th February 2022) - Rothfus, Gerard J
Abstract: In 'An argument against causal decision theory', Jack Spencer shows that standard formulations of causal decision theory run afoul of his Guaranteed Principle. In the sequential choice problem he employs to make this case, the transgression stems from an awkward discrepancy between how causalists typically value present vs future acts. This note suggests a version of causal decision theory that avoids this incongruity and so respects the Guaranteed Principle in Spencer's problem. However, this formulation, and hence symmetric appraisal of present and future acts, is also shown to be insufficient to secure causalist satisfaction of the Guaranteed Principle in general.